Mapping edo state university’s undergraduates’ awareness and usage of the new media - Obinna Johnkennedy Chukwu; Ata Awaji Anthony Reuben (Journal of Management and Science, 2022)
The study was carried out to map Edo State University undergraduates’ awareness and usage of the new media. The study was predicated on one theory - Technology Acceptance Model (TAM). The objectives, among other things, were to ascertain the extent of awareness and usage of new media in Edo State University; and the constraints they (undergraduate students) encounter, in respect to the usage of the media. Survey was adopted as the study design, while questionnaire was used to elicit information from 210 undergraduate students. Findings showed that the extent of awareness and usage of new media in Edo State University is high. The findings indicate also, amongst others, that the undergraduate students of the Institution did not encounter challenges in respect to usage of the new media. Based on the forgoing, it was recommended, amongst others, that the use of new media in pedagogy be introduced in schools, particularly, tertiary institutions in Nigeria, given the effectiveness of the use new media for teaching and learning in Edo State University, Uzairue, Nigeria. Further, efforts should be geared toward training undergraduate students on how to utilise new media for educational purposes.